2011
DOI: 10.1177/1362361311418690
|View full text |Cite
|
Sign up to set email alerts
|

Autobiographical memory in adults with autism spectrum disorder: The role of depressed mood, rumination, working memory and theory of mind

Abstract: Autobiographical memory difficulties have been widely reported in adults with autism spectrum disorder (ASD). The aim of the current study was to explore the potential correlates of autobiographical memory performance (including depressed mood, rumination, working memory and theory of mind) in adults with ASD, relative to a group of typical adults matched for age, gender and IQ. Results demonstrated that the adults with ASD reported higher levels of depressed mood and rumination than the typical adults, and al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
63
2
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 50 publications
12
63
2
1
Order By: Relevance
“…Scores for each question were summed to give a total score that indicated severity of mood: minimal depression (score of 0-9), mild depression (score of 10-18), moderate depression (score of 19-29) and severe depression (score of 30-63). Although not specifically designed for an ASD sample, this tool has been used previously in research with adults with high-functioning ASD (e.g., Berthoz, Lalanne, Crane & Hill, 2013;Crane, Goddard, & Pring, 2013). …”
Section: Adult Asd Diagnosis Survey 13mentioning
confidence: 99%
“…Scores for each question were summed to give a total score that indicated severity of mood: minimal depression (score of 0-9), mild depression (score of 10-18), moderate depression (score of 19-29) and severe depression (score of 30-63). Although not specifically designed for an ASD sample, this tool has been used previously in research with adults with high-functioning ASD (e.g., Berthoz, Lalanne, Crane & Hill, 2013;Crane, Goddard, & Pring, 2013). …”
Section: Adult Asd Diagnosis Survey 13mentioning
confidence: 99%
“…One exception is the study by Crane, Goddard and Pring, (2013) in which they failed to find gender differences in autobiographical memory in adults. However, the post hoc nature of the analysis meant that important variables such as IQ and age were not controlled.…”
mentioning
confidence: 91%
“…Enhanced verbal and emotional processing may also underlie gender differences in autobiographical memory in ASD since these factors have been demonstrated as important correlates of performance in this group. Goddard et al (2013) demonstrated deficits in the ability to recall both semantic and episodic autobiographical memories across the lifespan in children with ASD. Performance on these indices was predicted by verbal fluency and cognitive flexibility.…”
mentioning
confidence: 99%
See 2 more Smart Citations